COVID-19 Pandemic Management Policy: Different Approaches - Douki, Stamatina; Douki, Niki Christina (HAPSc Policy Briefs Series, 2022)
The rapid spread of SarsCoV-2 virus has challenged the sustainability of health systems worldwide, in terms of infection prevention, emergency management and effective strategies to protect public health. The present study aims to review and compose the existing international literature, which lists the different approaches of policy management of COVID-19 pandemic. The methodology included literature and research data review, which were collected through Google Scholar, Pub-med online database, articles, journals and books. This study makes evident that the analysis of all different approaches of the pandemic policy management will contribute significantly to its holistic treatment, by integrating best practices, in order to implement appropriate consultation programs as well as to reduce the negative consequences.